The genome sequence of the European conger eel, Conger conger (Linnaeus, 1758) [version 1; peer review: 3 approved] - Patrick Adkins; Rachel Brittain; Joanna Harley; Vengamanaidu Modepali (Wellcome Open Research, 2024)
We present a genome assembly from an individual Conger conger (the European conger eel; Chordata; Actinopteri; Anguilliformes; Congridae). The genome sequence spans 1,136.40 megabases. Most of the assembly is scaffolded into 19 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 18.86 kilobases in length.